2011
DOI: 10.1027/0269-8803/a000061
|View full text |Cite
|
Sign up to set email alerts
|

Brain and Body

Abstract: The temporal dynamics of electroencephalogram (EEG)-vigilance as a measure of tonic cortical arousal are discussed as pathogenetic factors in neuropsychiatric disorders. Although there is broad knowledge about the interaction of cortical arousal and activity of the autonomous nervous system (ANS) during different sleep stages, the association and temporal interaction between fine-graded EEG-vigilance stages and markers of sympathetic and parasympathetic activity during the transition from wakefulness to sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 57 publications
4
19
0
Order By: Relevance
“…This finding is in line with the study findings from Olbrich et al [11] and more recently by Jawinski et al [28], who demonstrated a gradual change of ANS activity in different states of brain arousal in 15-min resting EEG data. Most importantly, these gradual ANS changes were present in most cases within each 30-min time block.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is in line with the study findings from Olbrich et al [11] and more recently by Jawinski et al [28], who demonstrated a gradual change of ANS activity in different states of brain arousal in 15-min resting EEG data. Most importantly, these gradual ANS changes were present in most cases within each 30-min time block.…”
Section: Discussionsupporting
confidence: 93%
“…Earlier versions of VIGALL have been validated using EEG-fMRI data [10], in a PET study [23], against evoked potentials [24] and relating ANS parameters to different EEG-vigilance stages [11]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect on the psychiatric symptoms therefore might be less attributable to the psychopharmacological impact on central active neurotransmitters, but on the normalization of sleep rhythms and consecutive change at the behavioural level as suggested by the "vigilance framework" [2]. Interestingly, within the presented case, not only CNS but also ANS parameters showed levels of higher arousal, which might be interpreted in line with the close association between ANS and CNS arousal markers [5,7,25]. Further, quetiapine has been shown to reduce HRV measures and thereby probably increase sympathetic tone in a psychiatric cohort [26].…”
Section: Discussionsupporting
confidence: 67%
“…By measuring the topographic distribution and spectral composition of electroencephalic activity as well as the presence of slow eye movements, VIGALL enables the objective classification of so-called stages of vigilance (brain arousal), ranging from focused wakefulness via relaxed wakefulness and drowsiness to sleep onset [31,32]. It has been validated in a simultaneous EEG/fMRI study [33], in a PET study [34] and with parameters of the autonomous nervous system [35]. …”
Section: Introductionmentioning
confidence: 99%